Distribution of granulated fertilizers in dispensers mounted with single and double helicoidal - Gabriel Ganancini Zimmermann; Samir Paulo Jasper; Daniel Savi; Fernanda Gonçalves Moreno (Ciência Rural, 2024)
ABSTRACT: The high dependence of agriculture on fertilizers demands an improvement in the processes involved, with the purpose of environmental and economic sustainability. The objective was to compare the performance of helical dosing mechanisms with two formulations of granulated NPK fertilizers at three operating speeds. During the experiment, we used an electronic and automated bench to evaluate the performance of the single helical and double helical dosing mechanisms, in a completely randomized design. This bench measured the overflow of the two formulations of granulated NPK fertilizers (04-14-08 and 04-30-10) under different angular velocities (1.11; 1.94; and 2.77 m s-1). On the tests, we collected flow data and submitted them to descriptive statistics, frequency histograms, and statistical process control. The single helical feeder, as the speed increased, exhibited greater homogeneity of granulated NPK fertilizer deposition, with 611 flaws ha-1 compared to 3763 flaws ha-1 in the double screw. Although, the speeds of 7.0 and 10.0 km h-1 generated an increase in the flow of both granular fertilizers, as expected, the 04-30-10 fertilizer obtained the most uniform distribution at the lowest speed.